PENGARUH KEPEMILIKAN MANAJERIAL, ARUS KAS OPERASI, TINGKAT HUTANG DAN UKURAN PERTUSAHAAN TERHADAP PERSISTENSI LABA: (Studi Empiris Pada Perusahaan Sektor Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022) - Rinny Meidiyustiani; Salsa Indriyani (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
Earnings persistence is a component of earnings quality. This study aims to determine the effect of managerial ownership, operating cash flow, debt levels and company size on earnings persistence. In this study population, namely property and real estate sector companies listed on the IDX in the period 2018 to 2022. In this study the sample selection technique used purposive sampling and obtained 17 companies included with a period of 5 years, 85 samples were observed. The research method of data analysis in this study was multiple regression analysis using SPSS v25.0. The results of this study indicate that operating cash flow has a positive and significant effect on earnings persistence. Meanwhile, managerial ownership, debt level and firm size have no effect on earnings persistence